Pengaruh Penyaluran Zakat Produktif Baznas Microfinance Desa terhadap Tingkat Pendapatan Mustahik - Munawar Haris; Hasriani Hasriani; Supriadi Muslimin (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2023)
This research examines the effect of productive zakat distribution of village microfinance BAZNAS on the level of mustahik income in Maros district. The main problem in this study is how the effect of the distribution of productive zakat baznas microfinance villages on the level of mustahik data collection. This study aims to determine the effect of the distribution of productive zakat baznas microfinance villages on the level of mustahik income. This study uses quantitative research methods with a research population of 335 people who have received productive zakat in the form of business capital baznas microfinance villages from 2019 to 2021. The sample of this study was taken by 77 people using the Slovin formula. The sampling technique is proportional random sampling. Data collection of this study through observation methods, questionnaires and documentation. The data analysis technique uses a data instrument test that includes a validity test and reliability test, a basic assumption test which includes a normality test and a linearity test, then a hypothesis test which includes a coefficient of determination test (R2), a simple linear regression test and a t test. The results of this study show that the distribution of productive zakat baznas microfinance villages has a positive effect on the level of mustahik income as evidenced by the results of the analysis using the coefficient of determination technique (R2) showing the coefficient between the variables of productive zakat distribution (X) and the level of mustahik income (Y) of 0.493 or 49.3%. In addition, the results of the t test showed a calculated t value (8.544) > t table (1.992), which means that H0 was rejected and Ha was accepted, significant and the effect of the distribution of productive zakat BAZNAS village microfinance on the mustahik income level of 49.3% while the rest was influenced by other factors outside this study.